(untitled) (Baghdad Science Journal, 2025)
197 vaginal swabs were collected from women of different ages. (60) Isolates of Candida albicans (30.4%) were obtained, and the other species of Candida represent (18.27%). Bacterial infections showed (41.11%), and infection with Trichomonas vaginalis was (2.03%). Ten isolates of C. albicans were chosen randomly for farther study which include two virulence factors tendency of adhesion wich showed a percentage of (52%) to(32%) , and the ability to produce phospholipaze enzyme and it’s activity which showed (50%) of the isolates have the ability to produce the enzyme in different degrees .